MORTAL KOMBAT 2 - Slater, Jeremy; Urban, Karl, 1972-; Rudolph, Adeline, 1995-; McNamee, Jessica, 1986-; Lawson, Josh, 1981- (Warner Bros. Entertainment, 2026)
New Line Cinema presents the highly anticipated new installment in the classic video game franchise, Mortal Kombat II. This time, the fan-favorite champions now backed by Johnny Cage himself face off in a final, lawless tournament to overthrow the reign of Shao Kahn, a tyrant who threatens the very existence of Earthrealm and his followers.